PRINSIP-PRINSIP PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM PERSPEKTIF AL-QUR’AN - Sofa, Mutiara (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
This writing explains about the principles of learning Islamic Religious Education sourced from the Qur'an and Hadith. Learning in Islam always pays attention to individual differences (alfarq al-fardiyyah). For educators, the learning process is an obligation that is worth worship, which will be accounted for before Allah SWT in the hereafter, so that in its implementation it must be serious in educating children. So that it makes a pious and pious child. The type of research used in this paper is library research, which is a type of research that limits its activities to library collection materials without the need to conduct field research. This study uses a descriptive analysis approach. The results of this study explain that the learning principles of Islamic Religious Education include: 1) Student centered learning, 2) Learning by doing, 3) Lifelong learning (long life education), 4) Learning through imitation (learning by impersonation), 5) Learning through habituation (learning by habituation). The specific approaches in learning Islamic Religious Education, namely: 1) Education by example, 2) Education by customs, 3) Education by advice, 4) Education by paying attention, 5) Education by giving punishment.